Static and dynamic performance evaluation of a 3-DOF spindle head using CAD–CAE integration methodology. (October 2016) - Ma, Yue; Niu, Wentie; Luo, Zhenjun; Yin, Fuwen; Huang, Tian
Abstract: Accurate and rapid modeling and performance evaluation over the entire workspace is a crucially important issue in the design optimization of parallel kinematic machines (PKMs), especially for those dedicated for high-speed machining where high rigidity and high dynamics are the essential requirements. By taking a 3-DOF spindle head named A3 head as an example, this paper presents a feature-based CAD–CAE integration methodology for the static and dynamic analyses of PKMs. The approach can be implemented by four steps: (1) creation of a parameterized geometric (CAD) model with analysis features in SolidWorks; (2) extraction of the features from the CAD model using the Application Programming Interface (API) available in SolidWorks; (3) formulation of a CAD model in SAMCEF by mapping the configuration features from SolidWorks to SAMCEF; and (4) conversion of the analysis features into a scripting language named Bacon for Finite Element Analysis (FEA). The merit of this approach lies in that the FE model at different configurations can be updated automatically in batch mode, and PKMs having different topologies can be modeled with ease thanks to the down to link/joint level featuring. The experiment is also carried out to verify the effectiveness of the proposed approach. Highlights: A feature-based CAD–CAE integration methodology for FE analysis of PKMs is proposed. FE modeling strategies of commonly used joints are presented. The static and dynamic behaviors of the A3 head are evaluated over its workspace. The proposed approach is verified to be effective by corresponding experiments.